The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.preghy.2017.07.142
|View full text |Cite
|
Sign up to set email alerts
|

Labor therapeutics and BMI as risk factors for postpartum preeclampsia: A case-control study

Abstract: Objectives This study aims at identifying associations between therapeutics used during labor and the occurrence of postpartum preeclampsia (PPPE), a poorly understood entity. Study Design and Main Outcome Measures This is a case-control study of women who received an ICD-9 code for PPPE (cases) during the years 2009–2011, compared to women with a normotensive term pregnancy, delivery and postpartum period until discharge (controls), matched on age (±1 year) and delivery date (± 3 months). Cases were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The etiology and pathogenesis of PE are not clear [ 3 ], which has been reported to be associated with abnormal trophoblast invasion resulting in maternal endothelial dysfunction, chronic placental malperfusion and hypertension with adverse outcomes [ 4 ]. With the exception of fetal and placental delivery, there is no specific therapy for PE [ 5 ]. Therefore, it is urgent to explore the therapeutic targets to improve the prognosis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology and pathogenesis of PE are not clear [ 3 ], which has been reported to be associated with abnormal trophoblast invasion resulting in maternal endothelial dysfunction, chronic placental malperfusion and hypertension with adverse outcomes [ 4 ]. With the exception of fetal and placental delivery, there is no specific therapy for PE [ 5 ]. Therefore, it is urgent to explore the therapeutic targets to improve the prognosis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies have not shown an increased risk of postpartum PE associated with the use of epidural anesthesia and pharmacologic agents that might be hypothesized to raise BP, such as vasopressors or ergot derivatives in labor or after delivery. 14,15 Clinical Presentation As noted earlier, postpartum PE can develop after a pregnancy with no antecedent diagnosis of a hypertensive disorder of pregnancy or after a pregnancy complicated by gestational hypertension or in women with underlying chronic hypertension. Approximately 60% of patients with new, delayed-onset postpartum PE have no antecedent diagnosis of a hypertensive disorder of pregnancy.…”
Section: Risk Factors Demographicsmentioning
confidence: 96%
“…8,13e16 Higher rates of intravenous (IV) fluid infusion on labor and delivery are also associated with an increased risk of postpartum PE. 15 To the best of our knowledge, published studies do not distinguish between prelabor cesarean deliveries and intrapartum cesarean deliveries, which would likely affect the amount of IV fluids administered. Women who receive greater volumes of IV crystalloids during labor and delivery may shift more fluid to the interstitial compartment and may subsequently be more likely to develop volume overload and hypertension when the fluid is remobilized to the intravascular space after delivery.…”
Section: Risk Factors Demographicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Elevated maternal pre-pregnancy BMI can lead to a higher risk of maternal and fetal morbidities and mortality [7][8][9][10][11][12][13]. It is controversial whether or not obesity impacts the response to assisted reproductive technology (ART) treatments [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%